She Matters : Women in Kazakhstan Corporate Leadership - International Finance Corporation (World Bank, Washington, DC, 2022)
This report makes a case for greater gender diversity on Kazakhstan corporate boards (including the board of directors and management board). Empirical evidence from around the world shows the importance and value of gender diversity in improving firms’ overall performance, including but not limited to financial performance. Gender diversity among business leaders typically leads to balanced decision-making processes, better monitoring and strategy involvement, and greater attention to environmental, social, and governance (ESG) issues to foster sustainability. This report analyzes the relationship between board gender diversity (defined as having at least 30 percent women on the board of directors) and the financial performance of Kazakhstan joint-stock companies (JSCs). For this purpose, a series of financial and gender indicators were collected from the data of the Bureau of National Statistics of the Agency for Strategic Planning and Reforms of the Republic of Kazakhstan, the Depository of Financial Statements and the Register of State Enterprises and Institutions, Legal Entities with the State Participation in the Authorized Capital of the Ministry of Finance of the Republic of Kazakhstan, Central Securities Depository, etc. In total, the study includes financial and non-financial information from 788 JSCs between 2017-2019.